Self-efficacy for physical activity of people over 65 - Silvia López Alonso (INFAD, 2020)
Professionals and researchers studying the care received by people over 65 stand by the benefits of physical activity to improve the quality of live. However, their analyses and field work show very low involvement rates of this group in physical activity programmes, a high reluctance to participate and, when done, this behaviour is hardly maintained over time. It is well known that self-efficacy is relevant to carry out an action, but there is no evidence suggesting that the same is true for physical activity. This study aims to find out if self-efficacy improves the attitude of the elderly towards physical activity; to define self-efficacy as a construct; to design and validate a self-efficacy scale regarding physical activity for people over 65; to analyse the response of a representative sample of over 65s from Valencia to this construct; and to find out if gender and age affect self-efficacy in relation to physical activity.